The Consequences of Different Interpretations of the Rules on Vat for the Furniture Industry - Andrzejczak, Katarzyna (Studia Oeconomica Posnaniensia, 2015)
The lack of any mechanisms to ensure a uniform interpretation of tax law is a significant risk for the business activities of Polish enterprises. A disputed interpretation lasting more than two years, concerning the rate of tax on goods and services for installing furniture systems, is a current example of this problem. The Supreme Administrative Court can decide on disputes, and this is favoured by entrepreneurs as it can be the basis for applying for a tax refund as well as change the situation of the furniture market by reducing legal uncertainty and economic risk. The consequences of earlier divergent interpretations, however, affect both industry and consumers, who in many cases wrongly paid a higher price for the service received.